(untitled) (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2023)
Instant noodles are one of the people’s favorite foods in many countries, including Indonesia. ). The results of a survey by the Indonesian Consumers Foundation on 600 parents of kindergarten and elementary school students in five areas in Jakarta in 2014, showed that 93% of respondents stated that they often consumed instant noodles during the week. The aim of this research is to determine the application of Focus Group Discussion (FGD) in increasing elementary school (SD) students’ understanding of the dangers of consuming instant noodles. The method used in this research is qualitative. The habit of consuming instant noodles before the FGD was carried out was that several students consumed more than one pack of instant noodles in one day. The correct pattern of instant noodle consumption was able to be explained by all respondents. The conclusion of this research is that the understanding that elementary school students have after participating in the FGD shows changes in a good direction is reduce consumption of instant noodles.